A critical qualitative inquiry of the social practices of older adult gamblers. (20th October 2021) - Johnson, R; Pitt, H; Randle, M; Thomas, S
Abstract: Background: Older adults' participation in gambling is increasing internationally. Older adults have been identified as a group at greater risk of gambling harm. This may be due to their increased vulnerability due to life circumstances, such as retiring from paid work and social isolation. Current literature has focused on individual characteristics that may influence older adults gambling attitudes, behaviours, and experiences of harm, however, there has been little qualitative research that has explored other factors such as the influence of social practices surrounding gambling. This study explored how social practices influenced older adults' participation in gambling, and how these social practices may contribute to gambling risk. Methods: A critical qualitative inquiry was conducted and involved semi-structured phone interviews with 40 Australian adults aged 55 years and over. A Constructivist Grounded Theory approach was taken, and Social Practice Theory guided the thematic analysis of the data. Results: Two major themes were generated from the data. The first theme demonstrated that gambling was often embedded within older adults' social practices. For example, older adults would attend gambling venues with their social networks and engage in gambling as a way of building their social connection. Sometimes gambling occurred to try to meet the expectations of the wider social group, potentially increasing the risk of harm. Second, it was evident that gambling had become part a routine activity for older adults' everyday life. Conclusions: Older adults social practices related to gambling were linked with the accessibility and availability of gambling products in community environments. Interventions aimed at preventing and reducing gambling harm in older adults need to shift away from the individual and instead focus on disrupting social practices, including the routines associated with gambling. Key messages: Gambling was used by older adults to consolidate social connections and strengthen their sense of belonging within social groups and often involved routines around gambling. To prevent further harm from gambling to older adults, strategies should focus on the social context of older adults gambling rather than the individual characteristics of gamblers.